THE TRANSLATION OF ELLIPSIS AND EVENT REFERENCE IN JK ROWLING'S HARRY POTTER AND THE GOBLET OF FIRE - Adi Loka Sujono (Prasasti: Journal of Linguistics, 2016)
The study aims to investigate the translation of ellipsis and event reference in JK Rowling‘s‘ Harry Potter and the Goblet of Fire. In this present study, a qualitative content analysis method was employed. In translating the ellipsis and event reference, semantic and syntactic referents should be taken into account. Concerning with reference to eventualities, three forms of referents namely verb phrase ellipsis, so anaphora and pronominal event reference are analysed. Some adjustments such as literal translation, explicitation, omission, and the like are made.